Utilization of or Codes In Monitoring And Increasing The Effectiveness of Cocoa Farming Results In Sajau Village, Bulungan Regency - Natalia Susanti, Agnes; Kusumadiarti, Rini Suwartika (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This paper discusses the use of QR Code technology in monitoring and improving the efficiency of cocoa farming in Sajau Village, Bulungan Regency. The problem identified is the absence of an adequate monitoring system to manage cocoa farming in real-time. The research methodology used in this study is a descriptive method with a qualitative and quantitative approach to analyze data obtained from the field. using QR Code to track cocoa production and distribution data, which provides accurate information at high speed. The results of the study indicate that the application of QR Code can improve efficiency and transparency in the management of cocoa farming. In conclusion, QR Code is an effective solution to improve the management of cocoa farming in Sajau Village.